2014
DOI: 10.2147/dddt.s66576
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of nebulized delivery of linezolid, daptomycin, and vancomycin aerosol

Abstract: BackgroundAt this time, several antibiotics have been investigated as possibilities for aerosol administration, but local therapy has been found to be more efficient in several diseases.Materials and methodsThe drugs linezolid (Zyvox), vancomycin (Voncon), and daptomycin (Cubicin) were tested with three jet nebulizers with seven different residual cups and different loadings. Moreover, three ultrasound nebulizers were again tested with these drugs, with different loadings and mouthpiece attachments.ResultsWhen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…12, 13 This route of administration delivers a high concentration of drug to the lungs, while simultaneously bypassing the high systemic load needed to push drug concentrations to therapeutic levels in pulmonary tissues. Currently, this delivery method is accomplished by wet nebulization, which forms fine aerosol droplets of drug in-line with the ventilator for forced ventilator inhalation; however, the only option for pulmonary delivery of vancomycin is to administer a nebulized vancomycin that is only formulated and approved for IV use.…”
Section: Introductionmentioning
confidence: 99%
“…12, 13 This route of administration delivers a high concentration of drug to the lungs, while simultaneously bypassing the high systemic load needed to push drug concentrations to therapeutic levels in pulmonary tissues. Currently, this delivery method is accomplished by wet nebulization, which forms fine aerosol droplets of drug in-line with the ventilator for forced ventilator inhalation; however, the only option for pulmonary delivery of vancomycin is to administer a nebulized vancomycin that is only formulated and approved for IV use.…”
Section: Introductionmentioning
confidence: 99%
“…The major adverse effects were cough, dysgeusia, dysphonia, bronchospasm, pharyngitis, pneumothorax, tinnitus wheezing and hoarseness of voice. In the experiments by Zarogoulidis P. et al [9,48] with ampicillin-sulbactam, meropenem, ceftazidime, cefepime, piperacillin-tazobactam, linezolid, vancomycin and daptomycin it was observed that again the residual cup design along with specific jet-nebulizer compressor parameters were the most important factors affecting the small droplet production.…”
Section: Antibioticsmentioning
confidence: 98%
“…In the TRIUMPH trial treprostinil provided data where the 6-minute walking test was improved when compared to stable doses of bonsentan or sildenafil alone [15]. It has been previously investigated that different types and models of nebulisers in combination with different residual cup design and fillings affect the size of the aerosol production size [4,16,17]. The aim of this experiment was to investigate the possible administration of these drugs as aerosols and which would be the best equipment combination and residual cup filling.…”
Section: Introductionmentioning
confidence: 99%